Comparison of Short-Term Choroidal Thickness and Retinal Morphological Changes after Intravitreal Anti-VEGF Therapy with Ranibizumab or Aflibercept in Treatment-Naive Eyes. (4th March 2018) - Gharbiya, Magda; Giustolisi, Rosalia; Marchiori, Jessica; Bruscolini, Alice; Mallone, Fabiana; Fameli, Valeria; Nebbioso, Marcella; Abdolrahimzadeh, Solmaz
ABSTRACT: Purpose : To evaluate choroidal thickness (CT) and retinal morphological changes in eyes with neovascular age-related macular degeneration (nAMD) following ranibizumab or aflibercept intravitreal treatment. Materials and methods : This was a prospective, observational, comparative study where 76 eyes of 76 consecutive patients with treatment-naive nAMD were consecutively enrolled and randomized to ranibizumab 0.5 mg or aflibercept 2 mg injections. Spectral-domain optical coherence tomography images of the choroid were obtained by enhanced depth imaging modality. CT measurements were made of the subfoveal choroid, and at 500 μm from the center of the fovea in the superior, inferior, temporal, and nasal quadrants. Central subfield retinal thickness, intraretinal fluid, subretinal fluid, and pigment epithelium detachment were evaluated. Patients were followed up for 3 months. Results : Compared with baseline, CT decreased over time in both the ranibizumab and aflibercept group ( P = 0.04 and 0.001, respectively). At each location, the decrease in CT was significantly more prominent in aflibercept with respect to ranibizumab-treated eyes ( P < 0.05). Among the different choroidal neovascularization subtypes, type 3 lesions showed the greatest CT decrease after anti-vascular endothelial growth factor injections ( P = 0.003). Choroidal thinning was significantly greater in type 3 lesions treated with aflibercept compared with ranibizumab ( F = 13.6, P = 0.002). Post-treatment incidence of dry macula was higher in aflibercept- versus ranibizumab-treated eyes (50% vs. 76%, P = 0.03). Conclusions : CT reduction is greater in aflibercept-treated eyes, and type 3 lesions show the greatest thickness decrease. The post-treatment frequency of dry macula, evaluated by qualitative parameters, is higher in aflibercept-treated eyes, but is not correlated with CT change.